2007
DOI: 10.1038/ismej.2007.36
|View full text |Cite
|
Sign up to set email alerts
|

Public computer surfaces are reservoirs for methicillin-resistant staphylococci

Abstract: The role of computer keyboards used by students of a metropolitan university as reservoirs of antibiotic-resistant staphylococci was determined. Putative methicillin (oxacillin)-resistant staphylococci isolates were identified from keyboard swabs following a combination of biochemical and genetic analyses. Of 24 keyboards surveyed, 17 were contaminated with staphylococci that grew in the presence of oxacillin (2 mg l À1 ). Methicillin (oxacillin)-resistant Staphylococcus aureus (MRSA), -S. epidermidis (MRSE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 27 publications
4
36
1
Order By: Relevance
“…Escherichia coli were 100% resistant to tetracycline and penicillin, followed by augmentine (90%), ampicilin (85%), cefixime (65%), cloxacilline (65%), cotrimoxazole (65%), erythromycin (65%) and nalidixic acid (65%), but 70% susceptible to ceporex, followed by peflacine (65%) and ciprofloxacin (65%). This study is similar to the study of Issmat et al (2007) who isolated multi-drug resistant bacteria from public interfaces (computer surfaces). Occurrence of resistance in pathogens may reduce the effectiveness of previously useful antibiotics (Toroglu and Dincer, 2008).…”
Section: Discussionmentioning
confidence: 54%
“…Escherichia coli were 100% resistant to tetracycline and penicillin, followed by augmentine (90%), ampicilin (85%), cefixime (65%), cloxacilline (65%), cotrimoxazole (65%), erythromycin (65%) and nalidixic acid (65%), but 70% susceptible to ceporex, followed by peflacine (65%) and ciprofloxacin (65%). This study is similar to the study of Issmat et al (2007) who isolated multi-drug resistant bacteria from public interfaces (computer surfaces). Occurrence of resistance in pathogens may reduce the effectiveness of previously useful antibiotics (Toroglu and Dincer, 2008).…”
Section: Discussionmentioning
confidence: 54%
“…5% of samples. A handful of studies have used modern molecular ecological tools to investigate microbial communities on surfaces of public health significance [8,9], but to date, there have been no detailed molecular microbiology studies focused on the shopping mall food court environment.…”
mentioning
confidence: 99%
“…Our results suggest that MRSE persevered both in the unit and in medical personnel. Since it has been concluded that MRSE is a nosocomial infection, MRSE infections were probably contracted from a common source and the clones were transferred by patient-to-patient transmission [26][27][28][29][30]. As a result, a considerable number of medical workers will be examined from now on, even if colonization may be the source or the result of cross transmission.…”
Section: Discussionmentioning
confidence: 96%